Comparative Analysis of Public Administration of China and Indonesia - Akhmad Molki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to analyze the comparison of public administration between China and Indonesia with a focus on institutional structures, policy processes and public service mechanisms. The methodology used in this research is a descriptive qualitative approach with analysis of secondary data from various sources, including government reports, journal articles and academic publications. The research results show that public administration in China and Indonesia has significant differences in terms of institutional structure and policy processes. China, with its strong one-party government system, exhibits high levels of policy coordination and consistency. On the other hand, Indonesia with a multiparty democratic system shows greater flexibility and dynamism in the policy-making process. In terms of public service mechanisms, China tends to prioritize a top-down approach with a focus on efficiency and control, while Indonesia prioritizes a participatory approach with an emphasis on accountability and transparency. This research concludes that although there are fundamental differences in the public administration of the two countries, each system has its own advantages and challenges that can be used as lessons to improve the quality of public administration.